Species identification and the biological properties of several Japanese starfish - Sharmin, Farhana; Ishizaki, Shoichiro; Nagashima, Yuji (Asian Journal of Medical and Biological Research, 2017)
Marine organisms are a rich source of natural products with potential secondary metabolites that have great pharmacological activity. Starfish are known as by-catch products in the worldwide fishing industry and most of starfish have been got rid of by fire destruction without any utilization. On the other hand, starfish are considered as extremely rich sources of biological active compounds in terms of having pharmacological activity. In the present study, molecular identification of starfish species, micronutrient content and hemolytic activity from Luidia quinaria, Astropecten scoparius, and Patiria pectinifera were examined. Nucleotide sequence analysis of the 16S rRNA gene fragment of mitochondrial DNA indicated that partial sequences of PCR products of the species was identical with that of L. quinaria, A. scoparius, and P. pectinifera. From the results of micronutrient contents, there were no great differences on the micronutrient among species. However, Cd, Cu, and as contents had species-specificity. The crude extract of three starfish showed hemolytic activity against 2% rabbit erythrocytes with 50% hemolytic concentration of 10-1000 ?g/mL. The findings of the present study provided some basic information about identification of starfish species, potentialities of starfish which could be utilized in food and pharmaceutical industry. Asian J. Med. Biol. Res. December 2016, 2(4): 689-695